Diseño y construcción de un biodigestor para la generación de energía térmica y demostración de generación de energía eléctrica en el criadero porcino la bonita - Basurto Cusme, Carlos Antonio (2017)
"La Bonita" pig farm, located in Cotopaxi province, canton Latacunga, parish The Victory, Guapulo sector, with a total of 6 pigs that generate an amount of 10 kg/day of excreta disposal approximately. These Excreta were deposited in the adjacent field to the hatchery, which caused considerable environmental pollution. On the other hand, in the hatchery were consumed 15 kg/month of liquefied petroleum gas (LPG), in a gas stove for cooking food for pigs and for warming up the small ones, in two gas heaters. This LPG consumption is equivalent to an energy consumption of 1.3 kWh/day. In addition, there are 3 light bulbs of 100 W To which it is supplied with power via an extension from the house of the owner of the farm, with a consumption of 300 Wh/day....